Sustainable Value Chain Mapping of Downstream Aquaculture Fishery Products Based on Blue Economy - Achmad Andriyanto; Hilman Setiadi (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
Indonesia demonstrates considerable maritime potential; however, exploitation of the blue economy remains inadequate, particularly for aquaculture-derived products in Cirebon's coastal areas. As a central aquaculture hub in West Java, Cirebon faces persistent challenges in establishing sustainable value chains, characterized by insufficient value addition, fragmented stakeholder relationships, and incomplete adoption of the blue economy. This investigation pursues three objectives: (1) examining current value chain structures, (2) determining sustainability determinants, and (3) developing enhancement strategies. A mixed-methods analysis involving 190 participants from four sub-districts indicates promising opportunities but is constrained by economic, social, and environmental sustainability challenges. Processing stages yielded the highest value addition (42.4%), while aggregate sustainability was rated 2.67 (Moderately Sustainable), with social factors scoring highest (3.12) and having a positive impact on welfare. Economic-technological dimensions exhibited the strongest interdependence (r=0.675), which directly contributes to improving the economic performance of value chain actors. Establishing integrated fisheries industrial clusters emerged as the foremost strategic imperative for advancing blue-economy-oriented aquaculture downstream activities across Cirebon's coastal territories.